2016
DOI: 10.1007/s00066-016-0964-1
|View full text |Cite
|
Sign up to set email alerts
|

Baseline status and dose to the penile bulb predict impotence 1 year after radiotherapy for prostate cancer

Abstract: A significant reduction in the risk may be expected mainly when sparing the bulb in patients with no/mild baseline impotency (IIEF1-5 > 17).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Fractionation schedules were protocol defined and IMRT +/À IGRT was used in all cases. Our results are in accord with an interim analysis of the DUE-01 study which found maximum PB dose as a predictive factor for ED [21]. However, due to the small PB volume and potential substantial impact inter-observer contouring variability has on dose-volume parameters [19], we suggest that mean PB dose is likely to be a more robust metric for use in radiotherapy planning.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Fractionation schedules were protocol defined and IMRT +/À IGRT was used in all cases. Our results are in accord with an interim analysis of the DUE-01 study which found maximum PB dose as a predictive factor for ED [21]. However, due to the small PB volume and potential substantial impact inter-observer contouring variability has on dose-volume parameters [19], we suggest that mean PB dose is likely to be a more robust metric for use in radiotherapy planning.…”
Section: Discussionsupporting
confidence: 88%
“…The anterior border of the PB contour in the most cranial slice was used to guide the anterior border on the more caudal slices. Three-dimensional physical dose distributions were converted into equivalent dose in 2 Gy/f (EQD2) distributions by applying Withers formula [20] with a/b = 3 Gy [12,21] to each dose grid voxel. EQD2-based and physical dose-based PB dose-volume histogram data were exported from the analysis software.…”
Section: Penile Bulb Dosimetric Analysismentioning
confidence: 99%
“…Radiotherapy may negatively influence sexual functioning of patients, especially causing erectile dysfunction, and it is suggested that this fact is associated with the dose delivered to the penile bulb [ 23 , 24 ]. However, this seems to be less pronounced in modern radiotherapy techniques than with older ones.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors reported on the relationship between the dose to the anorectal or anal wall and the incidence of radiation proctitis symptoms [31][32][33][34]. Also, research by Nguyen showed that V60anterialwall was associated with a decrease in gastro-intestinal HRQoL [35]. However, no evidence exists on the relationship between the dose to specific anatomical regions and rectal pain or painful cramping.…”
Section: The Impact Of Rectal Discomfort On Hrqol and Possible Clinicmentioning
confidence: 99%
“…Impotence and orgasmic dysfunction are part of a patient's sexual functioning and have an impact on their and their partner's quality of life after prostate radiotherapy [33]. Recent studies [34,35] show that dose to the corpus cavernosum, the penile bulb and the total penile structure are predictive of a decreased sexual functioning after radiotherapy. Proton therapy may decrease the dose to the penile structures and may thereby offer the opportunity to even further enhance a patients' quality of life after radiotherapy.…”
Section: Genitourinary Side Effectsmentioning
confidence: 99%